Synthesis and binding properties of novel selective 5-HT3 receptor ligands - Modica Maria N. (BIOORGANIC & MEDICINAL CHEMISTRY, 2004)
This work reports on the synthesis and affinities for the 5-HT3 versus the 5-HT4 receptor of new piperazinyl-substituted thienopyrimidine derivatives 20-45 with a view to identify potent and selective ligands for the 5-HT3 receptor. Some of the new compounds show good affinity for the 5-HT3 receptor and, notably, do not display any affinity for the 5-HT4 receptor. 4-(4-Methyl-1-piperazinyl)-2-methylthio-6,7-dihydro-5H-cyclopenta[4,5] thieno [2,3-d]pyrimidine 31 exhibits the highest affinity for the 5-HT3 receptor (K-i = 33 nM) and behaves as noncompetitive antagonist. (C) 2004 Elsevier Ltd. All rights reserved.